Tradisi Marapulai Basuntiang di Inderapura Pesisir Selatan - Tuti Susanti; Jon Hendri; Weni Hamdina; Doni Aizus Idris; Siti Aisyah (CV. Alim's Publishing, 2024)
This research explores the Marapulai Basuntiang Tradition, a traditional Minangkabau wedding procession in Indrapura Pesisir Selatan, which is rich with symbolism and philosophical meaning. This tradition is not only a wedding ceremony, but also reflects the values of mutual cooperation, togetherness, and respect for ancestors. Through a qualitative approach and descriptive method, this research examines the stages of the Marapulai Basuntiang procession from preparation to post-event, as well as the changes that occur along with the influence of outside culture. It also compares the elements of the wedding in Pesisir Selatan with other regions to reveal how geographical, historical and socio-cultural factors influence the differences. The results of the study show that despite changes in traditional elements due to modernization, noble values and local cultural identity are maintained. This research aims to strengthen the understanding of the Marapulai Basuntiang tradition and provide recommendations for its preservation in the midst of modernization.